Efficient and safe auditable mixed-coin service scheme based on blind signature - Kang QIAO; Hongbo TANG; Wei YOU; Haitao LI (网络与信息安全学报)
The mixed-coin service can provide solutions for the privacy problem of blockchain,but it still faces efficiency bottlenecks and security risks.To further improve the efficiency and security protection of the mixed-coin service,an efficient and safe auditable mixed-coin service scheme based on blind signature was proposed.Firstly,this scheme added audit measures.It added an audit blockchain to the traditional mix-coin model to record the behavior of users and mixers,achieving traceability and accountability.Then,this method used elliptic curves algorithm to construct blind signatures instead of blind signature schemes based on bilinear pairs or RSA.Finally,this scheme proposed an auditable blind mix-coin service agreement based on the auditable mix-coin model and the blind signature algorithm based on elliptic curve.Simulation analysis shows that the proposed scheme has six security features,such as auditability and anti-theft attack,while providing privacy protection.Under the same security intensity,the proposed scheme can effectively reduce the computational overhead and storage overhead.